Socio-Economic Factors as a Cause of Children Dropout at Primary Level - Ghazi, Safdar Rehman; Ali, Riasat; Shahzad, Saqib; Shahzada, Gulap; Nawaz, Karim (Mediterranean Journal of Social Sciences, 2011)
Pakistan’s commitment to universal primary education by 2015 under EFA Framework appears elusive on currentperformance, as participation is low and drop-out rates continue to be high (Govt. of Pakistan, 2009). From the review of literature,social and economic factors were found as two main causes of children dropout; problem under study was to know about socio-economicfactors as a cause of children dropout at primary level. For the purpose, forty dropout children and their parents were interviewed usingstructured interview sheet of ten statements; five for social factors and five for economic factors. The collected data was tabulated, analyzedand interpreted in the light of the objectives of the study. Percentage was used to analyze the data as a statistical tool. Parents and childrenfrequency of responses with percentage on selected socio-economic factors was presented in tabular form. It was concluded that the parents’illiteracy and their consideration of education unfruitful for their children, their engagement in earnings, financial problems of the children,considering education as economic burden, engaging children in earning, and parents’ poor economic condition were the major areas whichcaused of their children dropout, and these areas provided sufficient basis for the recommendations of this study accordingly.